Macroeconomics. A European Text - Burda M. Michael (New York, Oxford University Press, 2005)
Building on the considerable success of previous editions, this fourth edition of Macroeconomics has been further simplified to provide an accessible yet comprehensive analysis of modern macroeconomics within both a European and a global context. Competing theoretical approaches are presented in a clear and balanced manner with continual reference to data and case study examples from the real world. Burda and Wyplosz have produced another excellent textbook that will guide students through challenging and complex issues with enhanced clarity and simplicity. Explanation of the objectives and procedures of the European Central Bank. Streamlined explanations of difficult topics to aid student understanding. Updated references to data and case studies from the real world. New epilogue presenting the evolution of macroeconomics. Excellent learning aids including chapter overviews, key concept summaries, and many new end of chapter exercises